THE INFLUENCE OF INVESTMENT, LABOR, AND TECHNOLOGY ON REGIONAL INCOME AND INEQUALITY - Fathonah, Ainnur; Aji Suseno, Deky (Business and Economic Analysis Journal, 2024)
The purpose of this research is to analyze the effect of investment, capital expenditure, labor, and technology on GRDP per capita and income inequality in Indonesia. The analysis technique uses Structural Equation Modeling-Partial Least Square (SEM-PLS) processed with WarpPLS 8.0. The object of this research is 34 provinces in Indonesia in 2016-2022. The results showed that domestic investment, capital expenditure, labor productivity and technology, and information and communication development index positively affected GRDP per capita. Foreign investment and working population have no effect on GRDP per capita. Domestic investment and labor productivity harm income inequality. Technology, information, and communication development index positively affects income inequality. Foreign investment, capital expenditure, working population, and GRDP per capita do not affect income inequality.